2023
DOI: 10.3390/foods12224124
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Indentification of Auramine O Dyeing Adulteration in Dendrobium officinale, Saffron and Curcuma by SERS Raman Spectroscopy Combined with SSA-BP Neural Networks Model

Leilei Zhang,
Caihong Zhang,
Wenxuan Li
et al.

Abstract: (1) Background: Rapid and accurate determination of the content of the chemical dye Auramine O(AO) in traditional Chinese medicines (TCMs) is critical for controlling the quality of TCMs. (2) Methods: Firstly, various models were developed to detect AO content in Dendrobium officinale (D. officinale). Then, the detection of AO content in Saffron and Curcuma using the D. officinale training set as a calibration model. Finally, Saffron and Curcuma samples were added to the training set of D. officinale to predic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…For example, Jin et al [ 24 ] proposed a method to simultaneously detect low concentrations of potassium sorbate and lead in matsutake based on SERS and fluorescence spectroscopy, which can accurately predict the residual amounts of preservatives and heavy metals in matsutake, providing a reference for other food safety testing. Zhang et al [ 25 ] found that the combination of SERS and machine learning algorithms can effectively and quickly detect the content of Auramine O in various traditional Chinese medicines.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Jin et al [ 24 ] proposed a method to simultaneously detect low concentrations of potassium sorbate and lead in matsutake based on SERS and fluorescence spectroscopy, which can accurately predict the residual amounts of preservatives and heavy metals in matsutake, providing a reference for other food safety testing. Zhang et al [ 25 ] found that the combination of SERS and machine learning algorithms can effectively and quickly detect the content of Auramine O in various traditional Chinese medicines.…”
Section: Discussionmentioning
confidence: 99%